Sanctions or crashes? A mixed-method study of factors influencing general and concealed mobile phone use while driving. (March 2021) - Truelove, Verity; Oviedo-Trespalacios, Oscar; Freeman, James; Davey, Jeremy
Highlights: Deterrence-based theories were applied to concealed phone use while driving. Concealed phone use while driving engaged in more frequently than general phone use. Focus groups revealed reading messages while driving most common and easy to conceal. Legal enforcement can counterintuitively influence concealed phone use while driving. Punishment avoidance and perceptions of safety were highly correlated. Abstract: Research into phone use while driving has found that the threat of legal sanctions has limited effectiveness on reducing this behaviour, yet the impact of these countermeasures on concealed phone use has been frequently overlooked. This study sought to understand how legal enforcement and perceptions of safety influence concealed phone use while driving using a mixed methods approach. First, focus groups were conducted among young drivers aged between 17 and 25 years ( n  = 60). Observing police presence was identified as an effective deterrent, however it was also considered easy to evade detection. Reading messages while driving was the most common type of phone use while driving engaged in, and this behaviour can be considered easy to conceal; therefore, this behaviour was the focus of the subsequent quantitative study. A longitudinal repeated measures survey ( n  = 192) on young drivers was conducted 3 months apart to quantitatively examine the factors that influence subsequent engagement in concealed and general reading messages while driving. The results suggest that concealing the phone increases the incidence rates of phone use while driving behaviour. Punishment avoidance and perceptions of safety were: (a) highly correlated and (b) significantly predicted engagement in both concealed and general reading messages while driving. The results provide support for education campaigns that target perceptions of safety, as well as increasing apprehension certainty (e.g., via the implementation of cameras) in order for legal countermeasures to act as a larger deterrent, as opposed to counterintuitively influencing concealed phone use behaviour.